Influence of titanium sources on the microstructures and properties of Li2TiO3 ceramics prepared by hydrothermal method - Liu, Wei; Di, Jiao; Zhang, Wen; Xue, Lihong; Yan, Youwei (Fusion engineering and design, 2019)
The influence of titanium sources on the microstructures and properties of Li2TiO3 were investigated. The results show the hydrothermal synthesized α-Li2TiO3 is a metastable phase and would transform into β-Li2TiO3 phase during sintering. Compared with TiO2-hydrothermal synthesized powder, the TBT synthesized powder has better sintering activity. The relative density of ceramic pebbles can reach 84% when it was sintered at 800 °C for 3 h. The grain size and crush load are 0.62 μm and 35 N, respectively. The formation mechanisms during hydrothermal process are also discussed. Combined results of XRD and TEM, it is concluded that for TiO2 as titanium source, TiO2 particles first dissolve into the LiOH solution and then the dissolved TiOx− groups react with Li+ to form Li2TiO3 precipitates. While for TBT source, α-Li2TiO3 nucleus immediately form as soon as TBT is added into the LiOH solution at room temperature.